Filamin A and Big2: A shared endocytic pathway - Sheen, Volney L. (Landes Bioscience, 2014)
Neural proliferation, migration and differentiation require reorganization of the actin cytoskeleton and regulation of vesicle trafficking to provide stability in maintaining cell adhesions, allow for changes in cell shape, and establishing cell polarity. Human disorders involving the actin-binding Filamin A (FLNA) and vesicle trafficking Brefeldin-associated guanine exchange factor 2 (BIG2 is encoded by the ARFGEF2 gene) proteins are implicated in these various developmental processes, resulting in a malformation of cortical development called periventricular heterotopia (nodules along the ventricular lining) and microcephaly (small brain). Here we discuss several recent reports from our laboratory that demonstrate a shared role for both proteins in actin-associated vesicle trafficking, which is required to maintain the expression and stability of cell adhesion and cell cycle associated molecules during cortical development. While changes in FLNA and BIG2 have first been linked to disorders involving the central nervous system, increasing reports suggest they are associated with aberrant development of various other organ systems in the body. These studies suggest that vesicle trafficking defects in FLN-GEF dependent pathways may contribute to a much broader phenotype than previously realized.